MANAJEMEN PRODUKSI PROGRAM DIALOG SAPA RIAU DI KOMPAS TV RIAU - Punty "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Sapa Riau on Kompas TV Riau is a dialogue program about events in Riau, especially Pekanbaru and its surroundings. Sapa Riau presents competent speakers in direct dialogue. The purpose of this study was to determine the planning, organizing, implementation and monitoring of production in the Sapa Riau dialogue program on Kompas TV Riau.This research uses descriptive qualitative method. This research was conducted at Kompas TV Riau Jalan Merak 83 B, Tangkerang Tengah, Marpoyan Damai, Pekanbaru City, Riau. There were 4 informants in this study who were taken based on a purposive technique. The collection technique in this research is through observation, interviews, and documentation. Data analysis techniques are collecting all data, reducing data, presenting, describing data. To test the validity of the data, researchers used participation extension and triangulation.The results of this study describe how the implementation of planning, organizing, actuating, and controlling (POAC) in the production management of the Sapa Riau dialogue program on Kompas TV Riau. Sapa Riau implements 4 stages: (1) planning which is carried out in two forms, namely, content / theme planning and time planning. (2) organizing (organizing) Sapa Riau has determined work placements according to expertise. (3) actuating (implementation) of Sapa Riau begins with making a rundown, shooting by taping, editing, and broadcasting the Sapa Riau program. (4) controlling (supervision) carried out by Sapa Riau, one of which was at the projection and evaluation meeting. The whole series of processes is a form of management in the production process of the Sapa Riau dialogue program.Keywords : production management, Kompas TV Riau, Sapa Riau.